CGIAR community of practice on gender-transformative research methodologies: Combining feminist approaches with CoP praxis to foster transformation - López, Diana E.; Bailey, Arwen (2023)
The adoption of a gender transformative agenda that embraces a feminist ethos can be particularly challenging in certain organizational cultures, especially those whose primary focus is not necessarily the attainment of gender equality. This presentation reflects about the development of a Community of Practice for Gender Transformative Research Methodologies (GTRM-CoP) within CGIAR, an influential agricultural research for development organization. Gender (and those ‘doing gender’) in CGIAR were not originally core to the work and mandate of the organization. Therefore, the recent identification of gender and social inclusion as a key impact area in CGIAR is a challenge. In the context of a predominant tradition of biophysical research, gender researchers have sometimes reported feeling like ‘support workers’ to fulfill the organizational obligation and donor requirements rather than having their own research agenda with a long-term vision and transformative objectives. While times have changed and awareness of the complex intersections between gender and agrifood systems has risen, budgets and capacity within CGIAR have not always kept pace with the new needs. Gender researchers continue to struggle to mainstream their insights into the core workings of CGIAR. We use the GTRM-CoP as a case study to show how taking a social learning ‘design turn’ can provide a space for transformative feminist ‘reflecting and doing’ and for building commitment and capacity for gender transformative research within the organization. Our presentation will first introduce CoPs as spaces for social learning that allow and strengthen individual and collective empowerment. This will be followed by an overview of attempts to mainstream gender in CGIAR. This helps contextualize the case study and locate it within more recent efforts to advance a gender-transformative agenda in the organization. The ongoing ‘reflecting and doing’ process of the GTRM-CoP is examined according to a set of design considerations that were adopted as part of a social learning praxis with the aim of creating the conditions for action-oriented learning. Our ‘reflecting and doing’ learning process is informed by feminist thinking and critical insights generated from recent debates about the role of the researcher and of research impacts vis-à-vis neo-colonialism. We conclude with critical reflections about emerging limitations as well as expanded ambitions of the GTRM-CoP as well as its potential for enticing broader gender institutional transformations.